The sister diaries - Quinn, Karen (Pocket Books, 2009)
Although they couldn't be more different, Amanda, Serena and Laura Moon have always been there for one another. Amanda sizzles in the high stakes arena of New York City real estate - but drags herself home each night to a cold, empty bed. From top executive at Prada, Serena is now an over-the-top stay-at-home Mum, plunging her marriage into crisis and her four-year-old into therapy. Laura spent the last six years caring for their dying mother. Now she is trying to breathe new life into her abandoned music career. Emotions explode when the sisters learn that their mother left everything - the multi-million dollar family home and a priceless painting - to Serena. But why? In an effort to make sense of the bequest, the girls journey to glamorous East Hampton to unravel the mystery behind their mother's past, setting off a chain of events that threatens the very core of their sisterhood.